'I need to switch the job'. Young rural-urban migrants' perceptions about their job during their education to work transition. Issue 4 (19th May 2023) - Basnet, Neha; Timmerman, Margaretha C.; van der Linden, Josje
ABSTRACT: Young people's choices and decisions during their education to work transition reflect their perceptions about work. Empirical studies of these perceptions of young rural-urban migrants are limited. This article explores the perceptions of young rural-urban migrants working at call centres in Kathmandu and the way these perceptions are associated with socio-cultural values and beliefs. The dominant perceptions found among young rural-urban migrants were that their job in a call centre served for skills development, financial needs, and as a temporary solution. Even though the centre was a fun place to work, there was little indication that young people saw this job as a 'career' The perceptions reveal a strong relation with socio-cultural values and beliefs influencing young people's choices and decision making in their education to work transition in this context.